Treatment with Octreotide in Patients with Well-Differentiated Neuroendocrine Tumors of the Ileum: Prognostic Stratification with Ga-68-DOTA-TATE Positron Emission Tomography - Walter Koch; Christoph J. Auernhammer; Julia Geisler; Christine Spitzweg; Clemens C. Cyran; Harun Ilhan; Peter Bartenstein; Alexander R. Haug (Molecular Imaging)
We investigated the use of Ga-68-DOTA-Tyr 3 -octreotate (Ga-68-DOTA-TATE) positron emission tomography (PET) and standardized uptake values (SUVs) to predict the effectiveness of treatment with the somatostatin analogue octreotide acetate (Sandostatin LAR) in patients with neuroendocrine tumors (NETs). Thirty patients with well-differentiated NETs of the ileum (grades G1 and G2) were studied with Ga-68-DOTA-TATE. The average SUV of a 50% isocontour volume of interest covering the lesion with maximum uptake (SUV mean ) and the maximum SUV (SUV max ) were determined. Patients were followed up, and the time to progression was recorded. Twenty-one patients showed progressive disease at the end of the study; nine patients had stable disease. The median progression-free survival (PFS) was 51.0 weeks (95% confidence interval [CI] 26.4-75.6). A cutoff for the SUV max of 29.4 and for the SUV mean of 20.3 could separate between patients with a long PFS (69.0 weeks; 95% CI 9.8-128.2) and a short PFS (26.0 weeks; 95% CI 8.7-43.3) response to octreotide acetate therapy. Patients with high radiotracer uptake had significantly higher PFS with a 2.9-fold higher chance for stable disease after 45 weeks; however, the prognostic performance of SUV max on an individual basis was poor, with a sensitivity of 75% and a specificity of 64%. SUV max and SUV mean of NET tumor lesions in Ga-68-DOTA-TATE PET are important prognostic indices for predicting the response to therapy with octreotide acetate.